2018
DOI: 10.1111/apt.15073
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: Bifidobacterium lactis NCC2818 probiotic vs placebo, and impact on gut transit time, symptoms, and gut microbiology in chronic constipation

Abstract: Summary Background Constipation is a prevalent gastrointestinal disorder. Patient dissatisfaction with prescribed medications is common, and there is need for alternative management strategies. Evidence shows that Bifidobacterium species may be beneficial in constipation. Aim To investigate changes in physiological and clinical measures of gut function in patients with chronic constipation following the consumption of Bifidobacterium lactis NCC2818, compared to placebo. Methods Participants were randomised to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 47 publications
(105 reference statements)
1
43
1
4
Order By: Relevance
“…We established an accurate Bayesian statistical model to estimate the bowel movement frequency-increasing effect due to B. longum BB536 intake, and this model revealed which subjects were responders or NRs in this study. This model enabled us to detect shortening of the bowel movement interval due to the intake of B. longum BB536, which is consistent with previous research [15,16]. In addition, because Bayesian estimation of the parameters enabled us to calculate a correct interval, this model achieved accurate quantitative evaluation of the effect of B. longum BB536 intake on bowel movement frequency, which has been difficult to achieve by threshold-based responder estimation [21].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We established an accurate Bayesian statistical model to estimate the bowel movement frequency-increasing effect due to B. longum BB536 intake, and this model revealed which subjects were responders or NRs in this study. This model enabled us to detect shortening of the bowel movement interval due to the intake of B. longum BB536, which is consistent with previous research [15,16]. In addition, because Bayesian estimation of the parameters enabled us to calculate a correct interval, this model achieved accurate quantitative evaluation of the effect of B. longum BB536 intake on bowel movement frequency, which has been difficult to achieve by threshold-based responder estimation [21].…”
Section: Discussionsupporting
confidence: 85%
“…Bifidobacterium is a representative microbial genus of probiotics that is frequently used to regulate bowel movements [10]. Multiple randomized controlled trials have shown that bifidobacteria intake increases bowel movement frequency [11][12][13][14] or shortens gut transit time [15,16]. However, the response to bifidobacteria supplementation varies from subject to subject.…”
Section: Introductionmentioning
confidence: 99%
“…Although the impact of probiotics on the microbiota in constipation is not well understood, a small number of trials have demonstrated significant changes in gut microbiota composition following probiotic supplementation (16) . For example, supplementation of Bifidobacterium lactis GCL2505 or Lactobacillus casei Shirota increased concentration of bifidobacteria, however B. lactis NCC2818 and VSL#3, a multi-strain probiotic, had no impact on gut microbiota composition (19)(20)(21)(22) . These results suggest that administration of probiotics may impact on certain microbiota components, but it is yet to be determined what impact this change has on constipation, and whether effects are mediated through microbiota modification or other mechanisms.…”
Section: Several Studies Have Demonstrated Differences In the Gut Micmentioning
confidence: 99%
“…Estudos com probióticos e prebióticos na constipação idiopática crônica. Research, Society and Development, v. 9, n. 10, e6459109071, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.9071 referidos como validados, em combinação com a escala de Bristol ou com outros questionários ou, ainda, de forma isolada (Yoon et al, 2018;Ibarra et al, 2018;Dimidi et al, 2019). Três ensaios analisaram o tempo de trânsito colônico com marcador radiopaco (Magro et al, 2014;Ibarra et al, 2018;Dimidi et al, 2019) e dois empregaram a metodologia da autopercepção/autoavaliação dos sintomas pelos pacientes, por meio do uso de um diário de relato (Jayasimhan et al, 2013;Glibowski et al, 2020).…”
Section: Constipação Idiopática Crônica (Cic)unclassified